Mono‐ and binuclear tris(3‐tert‐butyl‐2‐sulfanylidene‐1H‐imidazol‐1‐yl)hydroborate bismuth(III) dichloride complexes: a soft scorpionate ligand can coordinate to p‐block elements. Issue 11 (6th October 2016) - Fujisawa, Kiyoshi; Kuboniwa, Ayaka; Kiss, Mercedesz; Szilagyi, Robert K.
Abstract : The structure of a new mononuclear bismuth(III) complex with the soft scorpionate (3‐ tert ‐butyl‐2‐sulfanylidene‐1 H ‐imidazol‐1‐yl)hydroborate ligand is compared with that of the binuclear derivative. Abstract : Tris(pyrazolyl)hydroborate ligands have been utilized in the fields of inorganic and coordination chemistry due to the ease of introduction of steric and electronic substitutions at the pyrazole rings. The development and use of the tris(pyrazolyl)hydroborate ligand, called a `scorpionate', were pioneered by the late Professor Swiatoslaw Trofimenko. He developed a second generation for his ligand system by the introduction of 3‐ tert ‐butyl and 3‐phenyl substituents and this new ligand system accounted for many remarkable developments in inorganic and coordination chemistry in stabilizing monomeric species while maintaining an open coordination site. Bismuth is remarkably harmless among the toxic heavy metal p ‐block elements and is now becoming popular as a replacement for highly toxic metal elements, such as lead. Two bismuth(III) complexes of the anionic sulfur‐containing tripod tris(3‐ tert ‐butyl‐2‐sulfanylidene‐1 H ‐imidazol‐1‐yl)hydroborate ligand were prepared. By recrystallization from MeOH/CH2 Cl2, orange crystals of dichlorido(methanol‐κ O )[tris(3‐ tert ‐butyl‐2‐sulfanylidene‐1 H ‐imidazol‐1‐yl‐κ S )hydroborato]bismuth(III), [Bi(C21 H34 BN6 S3 )Cl2 (CH4 O)], (I), were obtained, manifesting a mononuclear structure. By using a noncoordinating solvent, red crystals of the binuclear structure with bridging Cl atoms were obtained, namely di‐μ‐chlorido‐bis{chlorido[tris(3‐ tert ‐butyl‐2‐sulfanylidene‐1 H ‐imidazol‐1‐yl‐κ S )hydroborato]bismuth(III)}, [Bi2 (C21 H34 BN6 S3 )2 Cl4 ], (II). These complexes show Bi III S3 Cl2 O and Bi III S3 Cl3 coordination geometries with average Bi III —S bond lengths of 2.73 and 2.78 Å in (I) and (II), respectively. The overall Bi III coordination geometry is distorted octahedral due to stereochemically active lone pairs. The three Bi III —S bond lengths are almost equal in (I) but show considerable differences in (II), with one long and two shorter distances that also correlate with changes in the UV–Vis and 1 H NMR spectra. For direct measurements of the Bi—S/Cl coordination, ligand K‐edge X‐ray absorption measurements were carried out in combination with ground and excited‐state electronic structure analyses. For p ‐block elements, these sulfur‐containing ligands are useful for preparing the appropriate complexes due to their flexible coordination geometry.